Influence of Seasonal Vitamin D Changes on Clinical Manifestations of Rheumatoid Arthritis and Systemic Sclerosis - Cutolo, Maurizio; Soldano, Stefano; Sulli, Alberto; Smith, Vanessa; Gotelli, Emanuele (Frontiers in Immunology, 2021)
Vitamin D (1,25(OH)2D - calcitriol) is basically a steroid hormone with pleiotropic biologic effects and its impact on the regulation of immune system may influence several clinical conditions. Calcidiol (25OHD), as precursor of calcitriol, derives, for the most part (80%), from cutaneous cholesterol (7-dehydrocholesterol) under the action of UV-B (sun-light). Consequently, serum concentrations fluctuate during the year, following the circannual rhythm of sun exposition. We will update about the available evidences regarding the complex influence of seasonal vitamin D changes on two different chronic connective tissue diseases, namely rheumatoid arthritis (RA) and systemic sclerosis (SSc). Notably, RA is an emblematic model of autoimmune disease with prevalent joint inflammatory features, while SSc is mainly an autoimmune progressive pro-fibrotic disease. However, in both conditions, low serum concentrations of 25OHD are involved in the pathogenesis of the diseases and emerging data report their impact on clinical manifestations.